2020
DOI: 10.1021/acs.cgd.9b01492
|View full text |Cite
|
Sign up to set email alerts
|

Topology-Controlled Selective Fe3+ Binding in Water by δ-Peptides with a Dihydropyrimidinone-Containing Amino Acid

Abstract: The effect of topology on the structure, self-assembly, and selective Fe3+ binding of δ-peptides has been investigated. A series of δ-peptides with an amino acid containing dihydropyrimidinone and o-, m-, and p-aminobenzoic acids have been designed to study the structure–function relationship. A new amino acid containing dihydropyrimidinone was synthesized by the Biginelli reaction of ethyl acetoacetate, urea, and o-nitrobenzaldehyde followed by reduction with iron powder and acetic acid. X-ray crystallography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…We designed and developed peptide based functional materials. [40][41][42][43] We recently reported dipeptides with varying steric constraints which exhibited diverse self-assemblies and formed a selective metallogel of Cu(II), Zn(II) and Pb(II). 44 Herein, we report a simple protocol for the synthesis of ferrocene substituted benzoic acid, as well as an efficient synthetic approach towards a ferrocene appended peptide mimetic providing a high reaction rate, yield and purity of the target products.…”
Section: Introductionmentioning
confidence: 99%
“…We designed and developed peptide based functional materials. [40][41][42][43] We recently reported dipeptides with varying steric constraints which exhibited diverse self-assemblies and formed a selective metallogel of Cu(II), Zn(II) and Pb(II). 44 Herein, we report a simple protocol for the synthesis of ferrocene substituted benzoic acid, as well as an efficient synthetic approach towards a ferrocene appended peptide mimetic providing a high reaction rate, yield and purity of the target products.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, they discussed topology-governed solid-state self-assembly of δ-peptides bearing dihydropyrimidinone and ( o / m / p )-aminobenzoic acid and application in selective Fe 3+ ion binding. 9 Tai and his co-workers explored the formation of several nanostructures with Boc- m -ABA-Aib-OMe (Aib: 2-aminoisobutyric acid) under the treatment of various chemical and physical stimuli. 10 They further observed that the two isomeric dipeptides Boc- m -ABA-Aib-OMe and Boc-Aib- m -ABA-OMe created various structures.…”
Section: Introductionmentioning
confidence: 99%